Ricky Ricotta's Mighty Robot vs. the Voodoo Vultures from Venus : Ricky Ricotta #3 - Pilkey, Dav, 1966-; Santat, Dan; Pilkey, Dav, 1966- (New York, NY : Scholastic Inc., 2014)
A small mouse named Ricky Ricotta and his best friend, a giant flying robot, save the world from Victor Von Vulture and his vicious Voodoo Vultures from Venus.
"3"--Spine.
Originally published in 2001 in a slightly different form by Blue Sky Press under title: Ricky Ricotta's giant robot vs. the voodoo vultures from Venus.
Keywords: Ricotta, Ricky (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Robots -- Juvenile fiction; Heroes -- Juvenile fiction; Vultures -- Juvenile fiction; Mice -- Fiction; Robots -- Fiction; Heroes -- Fiction; Venus (Planet) -- Juvenile fiction; Humorous fiction